Enhanced Security Model for Information and Online Transaction Processing System Using Mandatory Access Control (MAC) Mechanism - Ononiwu Akanwa, Allwell; E. Ejiofor, Virginia (International Journal of Computer Sciences and Engineering, 2021)
With the increasing popularity of the internet as well as the evolving acceptance of cashless policy, information and online transaction processing systems are generally more susceptible to direct attack and abuse than their offline counterparts. Various security techniques have previously been developed to regularly assess the vulnerability of these systems and provide security to users. However, a number of these security techniques have proved to have bottlenecks thereby, putting sensitive financial information, services and products at risk of cyber-attacks. In this work, an enhanced security model that improves the security of the online transaction processing system is designed. This algorithm combines the features of Multilevel Security (MLS) and the Bell-Lapadulla model (BLM) to ensure the secure state of the system. Additionally, Mandatory Access Control (MAC) mechanism was used to enhance the security of the sensitive information/data shared during the online transaction processing. The methodology adopted was Object Oriented Hypermedia and Design Methodology (OOHDM) which is well suited for analyzing and designing objects that make up the new security enhanced system. Microsoft Visual Studio 2010 was used as our development environment. The programming language used was PHP and Java Script, while MySQL Server 2008 was used in the development of the database engine. Enhancing the security requirement(s) of the system was considered. The results showed that the enhanced security model using Mandatory Access Control (MAC) mechanism offered a highly secured system where users and organizations felt protected while carrying out transactions online.